ANALYSIS OF GOOD PRACTICES IN STEM EDUCATION IN THE SCHOOLS OF THE VELIKO TARNOVO REGION IN THE SECOND YEAR OF THE NATIONAL PROGRAM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the current National Program for the construction of STEM centres in the schools of Bulgaria, the basic parameters for the requirements for the construction of modern teaching laboratories, offices, etc. are laid down. 16 schools from the Veliko Tarnovo region have been approved for the various stages of the program and for the second year have successfully implemented training in the built STEM centres. The centres built in some of the schools, their orientation and their use in the education of the students are shown. In these schools, the newly built centres are already used by the teachers of the relevant subjects for training in modern conditions with the aim of increasing the success rate of the students and practical application of the acquired knowledge. Construction of such centres in other schools is also planned for the next academic year